Peluang Dan Ancaman Perdagangan Produk Pertanian Dan Kebijakan Untuk Mengatasinya : Studi Kasus Indonesia Dengan Thailand - Muhamad Nurul; Adi Nur Arif; Dafit Hidayat; Atikah Elnisa Fikri; Daspar (CV. ITTC INDONESIA, 2024)
In organizing to maintain the financial interface in a period of globalization, in which the number and actions of multinational corporations and transnational organizations are increasing, all countries in the region form economic alliances. The unification of all countries within the framework of a common showcase or the range of free exchanges is expanding. Worldwide law is the law that permits and controls political, economic, and other human relations across national borders. Their respective participations between Indonesia and Thailand were realized to meet the interface of the two countries. There are currently two Indonesian agent offices in Thailand. The main agent office is the Government of the Republic of Indonesia office in Bangkok, and currently the Department of the Republic of Indonesia (KRI) in Songkhla. The task of KRI Songkhla, which was most widely established in 1997, was to carry out consular relations in accordance with the 1963 Vienna Tradition. Keywords: Export, import, trade relations, international trade. To realize the establishment of this free trade area, ASEAN countries agreed to gradually remove trade barriers to form freer markets between member countries, including reducing import taxes on traded goods, through the removal of quota and non-tariff barriers. International exchange itself is also considered very important in international economic activities, especially in participation between Indonesia and Thailand. Thailand is Indonesia's largest trading partner in Southeast Asia and incorporates a long history of economic participation, particularly in universal exchange. Approving information from the Central Measurement Office (BPS), Thailand is included in Indonesia's 10 best exchange accomplices (Central Statistics Agency, 2018). One of the variables that strengthens participation between the two countries, in expanding into both within local Southeast Asia, is their commitment to ASEAN registration.